2009
DOI: 10.1007/s00468-009-0345-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of somatic embryogenesis in camphor tree (Cinnamomum camphora L.): osmotic stress and other factors affecting somatic embryo formation on hormone-free medium

Abstract: The aim of this study was to improve the direct somatic embryogenesis and initiate embryogenic callus formation in camphor tree (Cinnamomum camphora L.) on hormone-free medium. The influence of osmotic stress pretreatment of immature zygotic embryos (0.5 and 1.0 M solution of sucrose for 12, 24, 48, 72, 96, 120, and 144 h at 4 or 25°C) before cultured on hormone-free medium, on embryogenesis efficiency was assessed. The embryogenesis frequency was improved from 16.29 to 93.27%, while the average number of soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 51 publications
1
16
0
1
Order By: Relevance
“…Though highefficiency somatic embryo formation could be induced from immature zygotic embryos by sucrose pretreatment, and mature somatic embryos could be further regenerated into plantlets in camphor tree (Shi et al 2009), complete maturation of somatic embryos is considered the major bottleneck for plant regeneration. Application of ABA treatment promoted somatic embryo maturation in camphor tree, and maturation-treated somatic embryos achieved significantly improved germination frequency (Shi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though highefficiency somatic embryo formation could be induced from immature zygotic embryos by sucrose pretreatment, and mature somatic embryos could be further regenerated into plantlets in camphor tree (Shi et al 2009), complete maturation of somatic embryos is considered the major bottleneck for plant regeneration. Application of ABA treatment promoted somatic embryo maturation in camphor tree, and maturation-treated somatic embryos achieved significantly improved germination frequency (Shi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The fruits were surface-sterilized with 0.1 % (w/v) mercuric chloride (HgCl 2 ) solution for 10 min; immature zygotic embryos were isolated from the fruits and then pretreated with 0.5 M sucrose solution for 72 h; and somatic embryos were obtained by culturing the pretreated immature zygotic embryos on induction medium for 5 weeks as previously described (Shi et al 2009). Stems, young leaves, young flowers, and young fruits were collected from the same tree during March-May.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are able to enhance the maturation and germination because they can simulate the developmental environment of ZE (Te-chato and Hilae 2007). Shi et al (2009) in studies with Cinnamomum camphora L. found that the best results for SE maturation were obtained with concentrations varying from 20 to 50 g L -1 of sucrose, while higher concentrations, 70-90 g L -1 of sucrose, resulted in a decrease in the mean number of SE.…”
Section: Synchronization and Maturation Of Somatic Embryosmentioning
confidence: 98%
“…A la fecha no existen reportes de sistemas de embriogénesis somática en el género Litsea. En la familia Lauraceae hay reportes en este sentido para el laurel europeo (Laurus nobilis) (Canhoto et al, 1999), así como para los géneros Cinnamomum (Shi et al, 2009), Ocotea (Moura-Costa et al, 1993;Catarina et al, 2003) y Persea (Pliego-Alfaro, 1988).…”
Section: Introductionunclassified